Dispersive propagation of nuclear electromagnetic pulse in the ionosphere - Wei, Yongli; Zhu, Dinghan; Li, Zongxiang; Wang, Lihua; Wang, Yuan; Zhang, Tianchi; Xing, Bin; Cao, Baofeng; Li, Peng (Frontiers in Astronomy and Space Sciences, 2023)
On the propagation path to the satellite, the ionosphere will distort the nuclear electromagnetic pulse (NEMP) and changes its physical properties. This paper proposes a method for calculating the propagation of NEMP to the satellite. The method decomposes NEMP into the superposition of simple harmonic waves, and each simple harmonic wave is calculated separately in the ionosphere. With the consideration of different time of arrival and critical frequency of the ionosphere, the NEMP after propagating in the ionosphere is obtained by superposition of simple harmonic waves in time domain rather than the inverse Fourier transform which will erase the time domain information. The results show that NEMP is dispersive in ionosphere with the pulse broadened, the speeds changed and the bandwidth narrowed. The time-frequency spectrum can provide the frequency band where the signal energy is located. Our proposed method provides a simple and effective way to calculate the NEMP propagation in the ionosphere, which should afford help to the design of NEMP receivers and the selection of satellite orbit altitude.